Radioactive material containers (1950)
General view of assorted containers and components used to house radioactive materials. The jar labels include space to record the isotope, amount, and date. These containers are believed to have been used as part of U.S. Department of Agriculture research and testing, which commonly tested various uses of radioactive substances as fertilizer and used radioactive material to model the impacts of such material in soil and test the effectiveness of new insect control techniques or materials.
Keywords: United States. Bureau of Chemistry and Soils; Radioactive substances; Radioactive substances--Testing; United States. Department of Agriculture